COMPASSION SATISFACTION, SECONDARY TRAUMATIC STRESS AND BURNOUT AMONG RESCUERS - Zaidi, Syed Muhammad Imran Haider; Yaqoob, Nazia; Saeed, Husnain (Journal of Postgraduate Medical Institute, 2017)
Objective: To explore the level of and relationship between compassion satisfaction (CS), secondary traumatic stress (STS), and burnout (BO) and to find out significant predictors of compassion satisfaction among rescuers. Methodology: This study was based on cross-sectional survey research design. It was conducted in Faisalabad Division from September to December 2016. A sample of 185 men with mean age 32.45 ±5.64 paramedics (n=100) and firefighters (n=85) working in Rescue 1122 were selected with purposive sampling technique from Faisalabad and Chiniot City. Professional Quality of Life scale developed by Stamm (2009) was used to measure the level of CS, STS and BO among paramedics and fire fighters. Results: Significant positive relationship between CS and STS and significant negative relationship between CS and BO among rescuers were observed (p <0.01). Rescuers' have moderate level of CS, STS and BO. Compassion satisfaction was significantly predicted from age group, marital status, living area, socioeconomic status, nature of job, STS and BO (F [7,177] =44.37, p =.001) R2 =.64. Conclusion: Rescuers had average level of and significant relationship with CS, STS, and BO. Compassion satisfaction was significantly predicted from age group, marital status, living area, and socioeconomic status, nature of job, STS and BO.